Chemical composition of sediment and macrozoobenthos of small urban lakes, the Republic of Karelia, Russia - Evgeny Savosin; Zakhar Slukovskii (International Journal of Sediment Research)
Assessing the benthic communities in water bodies under increasing anthropogenic pressure seems to be an urgent task of scientific research aimed at short-term and long-term monitoring of water bodies. This study focuses on the chemical composition of modern sediment and the current state of macrozoobenthos of small lakes in the Republic of Karelia (Kitaiskoe and Plotichie) influenced by anthropogenic factors. It was discovered that the lakes of Medvezhyegorsk have a higher concentration of heavy metals (such as lead (Pb), cadmium (Cd), molybdenum (Mo), and antimony (Sb)) compared to the Earth’s crust and natural background levels. The current study established the significant impact of industry and transportation on the movement and build up of pollutants in these lakes. The qualitative and quantitative parameters analyzed for the benthic communities in the littoral and profundal zones included the species diversity, the structure of dominant species, and their percentage in the samples. According to the level of macrozoobenthos development, both reservoirs (lakes) were classified as mesotrophic, and according to the values of the chironomid index “K” as moderately polluted. The Pantle–Buck method (saprobic index) showed that the lakes can be classified as polluted (water quality class 4). Macrozoobenthos groups most tolerant to environmental conditions, for example, Chironomidae larvae, prevailed in the studied urban lakes. The economic development of the lakes leads to ecosystem transformation and long-term eutrophication over time affecting the biotic indicators of surface water quality. The results obtained can serve as a basis for complex environmental monitoring of the urbanized territories in the taiga zone.